2013
DOI: 10.2217/nnm.12.198
|View full text |Cite
|
Sign up to set email alerts
|

Ferumoxytol: A New, Clinically Applicable Label for Stem-Cell Tracking in Arthritic Joints with MRI

Abstract: Aim To develop a clinically applicable MRI technique for tracking stem cells in matrix-associated stem-cell implants, using the US FDA-approved iron supplement ferumoxytol. Materials & methods Ferumoxytol-labeling of adipose-derived stem cells (ADSCs) was optimized in vitro. A total of 11 rats with osteochondral defects of both femurs were implanted with ferumoxytol- or ferumoxides-labeled or unlabeled ADSCs, and underwent MRI up to 4 weeks post matrix-associated stem-cell implant. The signal-to-noise ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 61 publications
4
81
0
Order By: Relevance
“…In this study, we present Labeling MSC with ferumoxytol (Feraheme ® ), as described by Thu et al 65 (average NP load with $2.2 pg Fe per cell), 65 was not successful in our hands and did not result in a significant NP load per cell. This poor uptake of ferumoxytol, as also the uptake reported by other authors, [28][29][30] might not be sufficient to achieve single-cell detection by MRI as discussed in this report. Therefore, we chose MCP, VSOP, and Resovist ® to accomplish single-cell detection by MRI.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In this study, we present Labeling MSC with ferumoxytol (Feraheme ® ), as described by Thu et al 65 (average NP load with $2.2 pg Fe per cell), 65 was not successful in our hands and did not result in a significant NP load per cell. This poor uptake of ferumoxytol, as also the uptake reported by other authors, [28][29][30] might not be sufficient to achieve single-cell detection by MRI as discussed in this report. Therefore, we chose MCP, VSOP, and Resovist ® to accomplish single-cell detection by MRI.…”
Section: Discussionmentioning
confidence: 48%
“…To the best of our knowledge, the most sensitive MRI detection has been accomplished for 1,000 ferumoxytol-labeled cells after intracerebral implantation when cells were labeled with 2.2 pg Fe per cell. [27][28][29][30] However, no attempts have been made to visualize single cells with any of these approaches. Alternatively, Bulte 31 proposed in vivo labeling of MSC obtained by bone marrow (BM) aspiration from rats after prior IV injection with ferumoxytol.…”
Section: Introductionmentioning
confidence: 99%
“…56,60 Current strategies seem to be focused on off-label use of already FDA-approved components in generating a SPIO-based intracellular labelling agent. 56,61 The transfection agent poly-L-lysine was used to promote cellular uptake of the iron oxide nanoparticles. The transfection agent poly-L-lysine (Sigma, St Louis, MI) was used to promote cellular uptake of the iron oxide nanoparticles.…”
Section: Superparamagnetic Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Recent studies, however, have shown that iron oxide labeling, combined with magnetic targeting, might improve graft retention in the rat heart [29,30,34,36]. Thus, ferumoxytol cell labeling might have utility in both in vivo cardiac graft imaging and cell retention.…”
Section: Mri Of Labeled Hesc-cpcs In the Pig Heart ©Alphamed Press 2016mentioning
confidence: 99%